Understanding the Preferences and Considerations of the Public Towards Risk‐Stratified Screening for Colorectal Cancer: Insights From Think‐Aloud Interviews Based on a Discrete Choice Experiment - Rebecca A. Dennison; Reanna J. Clune; Stephen Morris; Chloe Thomas; Juliet A. Usher‐Smith (Wiley, 2024)
ABSTRACT Context Risk stratification has been suggested as a strategy for improving cancer screening. Any changes to existing programmes must be acceptable to the public. Objective This study aimed to explore the preferences and considerations of individuals relating to the introduction of different risk‐based strategies to determine eligibility for colorectal cancer (CRC) screening. Study Design Participants completed a discrete choice experiment (DCE) within online interviews. Nine conjoint‐analysis tasks were created, each with two potential CRC screening programmes. The attributes included personal risk of CRC, screening invitation strategy and impact. Participants chose between programmes while thinking aloud and sharing their thoughts. Transcripts were analysed using codebook thematic analysis. Participants Twenty participants based in England aged 40-79 years without previous cancer history or medical expertise. Results When choosing between programmes, participants first and primarily looked to prioritise saving lives. The harms associated with screening were viewed as a surprise but also felt by most to be inevitable; the benefits frequently outweighed, therefore, harms were considered less important. Risk stratification using individual characteristics was considered a nuanced approach to healthcare, which tended to be preferred over the age‐alone model. Detailed personal risk information could be taken more seriously than non‐personalised information to motivate behaviour change. Although it had minimal impact on decision‐making, not diverting resources for screening from elsewhere was valued. Individuals who chose not to provide health information were considered irresponsible, while it was important that those with no information to provide should not lose out. Conclusion Risk‐stratified CRC screening is generally aligned with public preferences, with decisions between possible stratification strategies dominated by saving lives. Even if attributes including risk factors, risk stratification strategy and risk communication contributed less to the overall decision to select certain programmes, some levels more clearly fulfilled public values; therefore, all these factors should be taken into consideration when redesigning and communicating CRC screening programmes. Patient or Public Contribution The primary data source for this study is interviews with 20 members of the public (current, past or future CRC screening invitees). Two public representatives contributed to planning this study, particularly the DCE.